(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
Skill acquisition has become the order of time given its importance in advancing global economy. This study examined the role of entrepreneurial skills’ acquisition in alleviating poverty. It is a descriptive survey design that permits holistic representation of variables engaged. Population of the study covers the entire NCE students of the Department of Business Education, Kwara State College of Education Oro, from which a sample size of 120 stratifiedly selected samples were selected. A well-structured questionnaire was adopted as the research instrument, which was validated by three Business Professors of the Kwara state University, Malete. Croribach Alpha formulae were used to test for the result reliability. Data collected were analyzed through Mean and Standard Deviation measurements. The study revealed that acquisition of entrepreneurial skills correlates and positively impacts poverty alleviation going by the mean statistical value evidence of 21.4%. In general, the study recommends that since acquisition of entrepreneurial skills is a function of poverty alleviation, the Nigerian government should embed into the existing institutional entrepreneurial projects, training programmes and the mechanisms to monitor and adjust them as trend may demand. Also, government should ensure the provision and sustainability of all required entrepreneurial training facilities in public schools (especially higher institutions) for this will assist government in redirecting the vision and interest of our youth towards jobs creation, self-reliance and nation building.